A fractal study for the effective electrolyte diffusion through charged porous media. (July 2019) - Liang, Mingchao; Fu, Chengguo; Xiao, Boqi; Luo, Liang; Wang, Zhankui
Highlights: A model is built for the effective electrolyte diffusion in porous media. Effects of microstructural and electrokinetic parameters are analyzed. Good agreement between our present model and results is observed. Abstract: Electrolyte diffusion in electrolyte solutions exists in various areas including rechargeable batteries, soil physics and chemical engineering. In this paper, a fractal model based on the capillary model and fractal theory of porous media is proposed to quantify the effective electrolyte diffusivity in porous media with consideration of the electrical double layer (EDL) effects. The present model explicitly relates to the micro-structural parameters of porous media and electrokinetic parameters. To validate this model, a comparison is carried out with experimental data and semi-analytical model results, and yields satisfying agreement. Besides, the influences of the parameters (the porosity, equivalent particle diameter, ratio of the minimum pore radius to the maximum pore radius, molar concentration, zeta potential, and dimensionless parameter β ) are discussed in details.